2015
DOI: 10.1016/j.ajog.2015.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Placental implantation abnormalities and risk of preterm delivery: a systematic review and metaanalysis

Abstract: We sought to evaluate the extent of the association between placental implantation abnormalities (PIA) and preterm delivery in singleton gestations. We conducted a systematic review of English-language articles published from 1980 onward using PubMed, MEDLINE, EMBASE, CINAHL, LILACS, and Google Scholar, and by identifying studies cited in the references of published articles. Search terms were PIA defined as ≥ 1 of the following: placenta previa, placenta accreta, vasa previa, and velamentous cord insertion. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 90 publications
5
102
0
3
Order By: Relevance
“…Much evidence now supports the hypothesis that the placenta plays a central role in determining pregnancy outcomes, and maternal and fetal health [16]. Current research, arising from life course perspectives [7] and the fetal origins hypothesis [8], has extended the placenta’s impact to predict adult chronic diseases [9], and potentially transgenerational effects [10].…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence now supports the hypothesis that the placenta plays a central role in determining pregnancy outcomes, and maternal and fetal health [16]. Current research, arising from life course perspectives [7] and the fetal origins hypothesis [8], has extended the placenta’s impact to predict adult chronic diseases [9], and potentially transgenerational effects [10].…”
Section: Introductionmentioning
confidence: 99%
“…This occurs mainly when the cervix is effaced and dilated and the membranes rupture spontaneously or are ruptured artificially. It can lead to rapid fetal exsanguination and death [1][2][3][4][5] and the perinatal mortality of undiagnosed VP has been reported to be as high as 60%. 6 The incidence of VP has been reported to range between in 1 in 1200 to 1 in 5000 pregnancies but the condition may have been under-reported.…”
Section: Resultsmentioning
confidence: 99%
“…6 The incidence of VP has been reported to range between in 1 in 1200 to 1 in 5000 pregnancies but the condition may have been under-reported. [1][2][3][4][5] A recent systematic review of 10 cohort studies found that the incidence of VP is 0.6 per 1000 pregnancies. 7 Approximately 90% of women presenting with a VP also have a velamentous cord insertion (VCI) and 3-4% of women presenting with a VCI have a VP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations